A STUDY OF THE OPTICAL PROPERTIES AND URBACH TAIL OF SPRAY-DEPOSITED TIO2 THIN FILMS AT DIFFERENT VOLUMES FOR OPTOELECTRONIC APPLICATIONS. - Tanko, Y; Onimisi, M.Y; Ali, H; Zakariya, B.Y.; Lawal, H.A; Kurawa , S.M (Global Journal of Chemistry, Biology and Physics (GJCBP), 2024)
In this study, titanium dioxioxide (TiO2) was produced stoichiometrically using an easier and cost-effective spray pyrolysis technique (SPT). The effect of microstructure and phase formation of TiO2 thin films at different volumes is investigated by XRD analysis. XRD investigation depicts that the TiO2 contents correspond to the anatase phase. XRD study also shows that the pure TiO2 at different content samples are nanostructured. A phase transition, anatase phase to mixed phase, was confirmed from the XRD when the TiO2 content increased (0.5, 1.0 1.5 and 2.0) cm3. A thorough investigation of microstructural and dispersion parameters was carried out. The results revealed that when the content concentration was increased from 0.5 to 2.0 at cm3, the crystallite size ranged from DS = 0.162 to 0.186 nm, δs = 38.104 to 28.90 nm, while the strain was found to decrease from ε = 2.933 to 0.7486, ×10-3. From the UV vis spectra, it is evident that the maximum absorbance values for different volumes of TiO2 (0.5, 1.0, 1.5, and 2.0) occur in the ultraviolet region at a wavelength of 300nm with a corresponding intensity of (-0.2 to 1.31) a.u., with absorption edges at the visible region of 400nm, shifted towards a longer wavelengths, resulting in the reduction of bandgap energy from 3.36eV to 3.27eV with corresponding decrease in the urbach energy displayed from 45.99eV to 12.30eV. The equivalent band tail contribution arising from the weak absorption tails with a maximum value obtained was 2.220 eV. The dispersion and oscillatory energy decrease abruptly with increasing TiO2 content, exhibiting the same phase of transition momentum. Other optical parameters like dielectric constants, refractive index, extension coefficient (k), absorption coefficient, and thermal conductivity are estimated.